Efektifitas Edukasi Self Management Terhadap Kontrol Tekanan Darah Pasien Hipertensi - Zada Amalia Agatha Sari Zada Amalia Agatha Sari; Novita Carolia; Rasmi Zakiah Oktarlina; Suharmanto Suharmanto (CV. Jasa Sukses Abadi, 2023)
Hypertension is a systolic blood pressure 140 mmHg or higher and a diastolic blood pressure 90 mmHg or higher.22 In 2020 WHO (Word Health Organization) reported that there were 1.13 billion cases of hypertension and has caused 9.4 million dead.22 At the United States, in 2017-2018 it was reported that 63% people over 60 years old suffered from hypertension with a higher percentage of women (66.8%) than men (58.5%).2 According to the 2018 RISKESDAS results patients with hypertension in the elderly amounted to 63.5%. Due to its high prevalence, hypertension is a major global health problem and the main cause of death and disability in the world every year.12 Treatment of hypertension is carried out for a long time so that the success of hypertension treatment is strongly influenced by self management of patients to adhere to the treatment, routinely checking blood pressure, increasing physical activity, reducing cunsumption of foods containing sodium.11 Self management of hypertension has an important role in effective control off blood pressure in patient with hypertension.3 One of the ways to increase knowledge related to the prevention and control of hypertension is through education.10 The education provided in the form of theoretical materials such as lectures, discussions, counseling, e-learning, and also practices such as workshops or training with various related topics. The materials provided is in the form of facts about hypertension such as definitions, signs and symptoms, risk factors, how to diagnose and treat them, normal blood pressure, hypertension prevention, complications, drug use, drug side effects, the importance of taking medication regulary, the importance of blood pressure checks periodically, diet, physical activity, relaxation techniques such as deep breathing, muscle relaxation, guided imagery.18